Are dual-purpose and male layer chickens more resilient against a low-protein-low-soybean diet than slow-growing broilers?. Issue 1 (2nd January 2020) - Kreuzer, M.; Müller, S.; Mazzolini, L.; Messikommer, R. E.; Gangnat, I. D. M.
ABSTRACT: 1. Although fattening dual-purpose types or male layer hybrid chickens appears more ethical than the common practice of culling day-old male layer chicks, the lower feed efficiency of these birds raises concerns. Replacing feed ingredients that compete with food production by those of lower value for human nutrition would be beneficial. 2. Lohmann Dual (LD), a modern dual-purpose type, Lohmann Brown (LB), a male layer hybrid, and Hubbard JA 957 (HU), a slow-growing broiler type, were fattened for nine weeks on two diets (control or −20% crude protein; n = 6 × 12 birds). Growth, carcass and meat quality were analysed. 3. Growth performance of HU exceeded that of LD and especially of LB. The growth depression caused by the low-protein diet fed to LD (−7%) was only half of that found in HU (−13%). The LD fed the control diet had the same feed efficiency as the HU fed the low-protein diet. Even the LB had a lower performance and feed efficiency with the low-protein diet in growth. There was a gradient in carcass properties (weight, dressing percentage, breast meat yield, breast proportion and breast angle) from HU to LD to LB, with some additional adverse effects of the low-protein diet especially in HU. There were some breed differences in fatty acid profile in the intramuscular fat. 4. In conclusion, the dual-purpose type used complied with regulations for Swiss organic poultry systems in terms of growth rate and was found to respond less when fed a low-protein diet than the slow-growing broiler type. The LB males were inferior in all growth and carcass quality traits. Future studies need to determine the exact protein and amino acid requirements of dual-purpose and layer hybrid chickens and the economic feasibility of the systems, especially for organic farming.